S-PVA / PVA PA11 affinity membrane as well as preparation method and application thereof in adsorption of bilirubin

By grafting chitosan on the nylon 11 membrane and coating s-PVA/PVA, an s-PVA/PVA PA11 affinity membrane with efficient adsorption of bilirubin was prepared, which solved the problem of insufficient biocompatibility of existing blood perfusion materials, and achieved efficient removal of bilirubin and good blood compatibility.

CN119549133APending Publication Date: 2025-03-04HONGSAIDIS (SUZHOU) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848734.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing blood perfusion materials such as activated carbon have biocompatibility problems, making it difficult to effectively remove harmful substances such as bilirubin in the blood, and may destroy red blood cells and cause thrombosis.

Method used

An s-PVA/PVA PA11 affinity membrane was used, which improved biocompatibility and adsorption capacity by grafting chitosan on a nylon 11 membrane and coating in different proportions of s-PVA/PVA.

Benefits of technology

It achieves efficient adsorption of bilirubin, improves the hydrophilicity and mechanical properties of the membrane, reduces porosity, enhances compatibility with blood, and reduces the risk of side reactions after adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549133A_ABST
    Figure CN119549133A_ABST
Patent Text Reader

Abstract

The invention discloses an s-PVA / PVA PA11 affinity membrane as well as a preparation method and application thereof in adsorption of bilirubin, and belongs to the technical field of preparation of affinity membranes. The invention successfully prepares the affinity membrane based on a nylon 11 (PA11) membrane which is highly compatible with a human body, and the biocompatibility of the affinity membrane is further enhanced by grafting chitosan. The film is coated by s-PVA / PVA in a ratio of 0: 2, 1: 4, 1: 2 and 1: 1. The inventor carries out detailed mechanical property and contact angle tests on the obtained affinity membrane. The result shows that when the mass ratio of the coating solution is 1: 1, the elongation at break of the prepared film is increased from 47% to 72%, and the contact angle is also reduced from 70 degrees to 30 degrees. Therefore, the prepared affinity membrane has excellent hydrophilic and mechanical properties, and is very suitable for adsorption test; the porosity is reduced from 0.94 to 0.59, which means that the porosity is relatively low, and the low porosity has obvious superiority in the aspect of adsorption and plays a significant role in promoting the adsorption process of bilirubin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of affinity membranes, and in particular relates to an s-PVA / PVA PA11 affinity membrane and a preparation method thereof and application of the membrane in adsorbing bilirubin. Background Art

[0002] Affinity membrane is a material that combines the advantages of membrane separation technology and affinity chromatography, and is mainly used to separate and purify biomacromolecules. It introduces specific affinity ligands into the membrane material, making the membrane highly selective and affinity for specific biomolecules. This technology can effectively solve the limitations of traditional powder or granular adsorbents in the mass transfer process, and due to its inherent structural characteristics, affinity membranes have a lower leakage risk than granular and powder materials.

[0003] To date, most membranes used for affinity separations are made of organic materials. In general, organic materials can be roughly divided into two categories, namely natural polymers and synthetic polymers. Natural macromolecular materials such as agarose, dextrin and chitosan (CS) are good affinity matrices because they are compatible with common ligands, but are often difficult to process into membranes. In contrast, synthetic polymers such as nylon, polysulfone and glycidyl methacrylate are easy to fabricate into membranes, but are not very suitable for immobilizing ligands due to their low compatibility and low concentration of active functional groups in their structure.

[0004] Bilirubin, as the main decomposition metabolite of hemoglobin, has been found to be a major hazard to human health in the past few decades. Bilirubin can easily cross cell membranes and cause damage to organs and even neural tissues. Once it passes through the blood-brain barrier and is deposited in the brain, it will cause brain damage. Hemoperfusion has become one of the most promising strategies for toxin removal due to its low cost and high efficiency. When blood passes through the hemoperfusion column, toxins in the blood can be removed by adsorption. The adsorption efficiency depends on the functional groups and structure of the adsorbent. Traditional hemoperfusion materials such as activated carbon (AC) have some biocompatibility issues: on the one hand, AC can adsorb a large amount of beneficial proteins such as human serum albumin as a hemoperfusion material; on the other hand, AC can easily destroy red blood cells in the blood during perfusion, causing hemolysis, and its fragments can also fall into the blood during flushing, inducing severe thrombosis. These defects limit the application of AC in hemoperfusion and prompt us to find more suitable materials.

[0005] Based on the above reasons, this application is hereby filed. Summary of the invention

[0006] In view of the problems or defects in the above-mentioned prior art, the object of the present invention is to provide an s-PVA / PVA PA11 affinity membrane and a preparation method thereof and an application thereof in adsorbing bilirubin.

[0007] In order to achieve the above-mentioned purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing an s-PVA / PVA PA11 affinity membrane, the method specifically comprising the following steps:

[0009] (1) Preparation of PA11 affinity membrane

[0010] Prepare an acetic acid solution of chitosan, adjust the pH value to 2, place the activated PA11 membrane in the acetic acid solution of chitosan, and react at room temperature for 0.5-1.5 hours; after the reaction is completed, filter under reduced pressure, dry, and wash to obtain the PA11 affinity membrane;

[0011] (2) Preparation of s-PVA / PVA coating solution

[0012] Mix sulfonated PVA (s-PVA), polyvinyl alcohol (PVA) and deionized water according to a ratio, heat and stir to mix, and obtain the s-PVA / PVA coating solution;

[0013] (3) Preparation of s-PVA / PVA PA11 affinity membrane

[0014] The pH value of the s-PVA / PVA coating solution in step (2) is adjusted to 1.5-2.5, and then glutaraldehyde (GA) is added according to the ratio, and the resulting mixed reaction solution undergoes a pre-crosslinking reaction at room temperature; after the pre-crosslinking reaction is completed, the resulting pre-crosslinking coating solution is coated on the surface of the PA11 affinity membrane in step (1), and finally the solution is sealed and dried at room temperature, and washed to obtain the s-PVA / PVA PA11 affinity membrane.

[0015] Furthermore, in the above technical solution, the concentration of chitosan in the chitosan acetic acid solution in step (1) is 0.5-2% (W / V). In a preferred embodiment of the present invention, the concentration of chitosan in the chitosan acetic acid solution is 1% (W / V).

[0016] Furthermore, in the above technical solution, the preparation method of the activated PA11 film in step (1) is as follows:

[0017] Formaldehyde and phosphoric acid are mixed according to a ratio, heated to 55-65° C., a PA11 membrane is placed in the resulting mixed solution, oscillated at a constant temperature for 5-10 hours, then cooled to 40-50° C., washed, and finally dried with filter paper to obtain the activated PA11 membrane.

[0018] Preferably, in the above technical solution, the volume ratio of formaldehyde to phosphoric acid is 100:1.

[0019] Furthermore, in the above technical solution, in a preferred embodiment of the present invention, the reaction time in step (1) is 1 hour.

[0020] Furthermore, in the above technical solution, in a preferred embodiment of the present invention, the drying temperature in step (1) is 90° C. and the drying time is 45 minutes.

[0021] Furthermore, in the above technical solution, the mass ratio of s-PVA to PVA in step (2) is 1:4-1:1. For example, it can be 1:4, 1:3, 1:2, 1:1. Preferably, it is 1:1.

[0022] Furthermore, in the above technical solution, the preparation method of s-PVA in step (2) is as follows:

[0023] PVA is mixed with anhydrous ethanol (EtOH) according to a ratio, heated to swell, and a PVA / EtOH mixture is obtained; then sodium hydroxide is added according to a ratio, mixed evenly, 1,3-propane sultone is added dropwise to the obtained mixture, and the heating reaction is continued for 6-10 hours after the addition is completed; after the reaction is completed, the s-PVA is obtained by washing with alcohol, filtering, and vacuum drying.

[0024] Preferably, in the above technical solution, the usage ratio of PVA to anhydrous ethanol (EtOH) is 10g:250mL.

[0025] Preferably, in the above technical solution, the mass ratio of PVA to sodium hydroxide is 10:(4-6).

[0026] Preferably, in the above technical solution, the mass ratio of PVA to 1,3-propane sultone is 10:1.

[0027] Preferably, in the above technical solution, the temperatures for the heating swelling and the heating reaction are both 75-85°C.

[0028] Furthermore, in the above technical solution, the concentration of the s-PVA / PVA coating solution in step (2) is 1-5wt%, preferably 2wt%.

[0029] Furthermore, in the above technical solution, the ratio of the molar amount of [-OH] to the molar amount of [GA] in the PVA in step (3) is 4:1.

[0030] Furthermore, in the above technical solution, the time of the pre-crosslinking reaction in step (3) is 15-25 minutes, preferably 20 minutes.

[0031] The second object of the present invention is to provide an s-PVA / PVA PA11 affinity membrane prepared by the above method.

[0032] The third object of the present invention is to provide the use of the s-PVA / PVA PA11 affinity membrane prepared by the above method in adsorbing bilirubin.

[0033] Furthermore, in the above technical solution, the application method is as follows: placing the s-PVA / PVA PA11 affinity membrane in a bilirubin solution, adjusting the pH value of the bilirubin solution to 7.4, heating to 22-42°C and shaking the solution for 2-3 hours; after the reaction is completed, filtering the solution.

[0034] Furthermore, in the above technical solution, the reaction temperature is preferably 37°C.

[0035] Furthermore, in the above technical solution, the concentration of the bilirubin solution is 10-50 mg / L, preferably 50 mg / L.

[0036] The present invention also provides an adsorbent for adsorbing bilirubin, wherein the adsorbent comprises the s-PVA / PVA PA11 affinity membrane prepared by the method described above.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention successfully manufactured an affinity membrane based on a nylon 11 (PA11) membrane that is highly compatible with the human body, and further enhanced its biocompatibility by grafting chitosan. The membrane was coated with s-PVA / PVA ratios of 0:2, 1:4, 1:2, and 1:1. The inventors conducted detailed mechanical property and contact angle tests on the obtained affinity membrane. The results showed that when the mass ratio of the coating solution was 1:1, the elongation at break of the prepared membrane increased from 47% to 72%, and the contact angle decreased from 70° to 30°. This shows that the prepared affinity membrane performs very well in both hydrophilic and mechanical properties and is very suitable for adsorption testing; the porosity is reduced from 0.94 to 0.59, which means that the porosity is relatively low. This low porosity has obvious advantages in adsorption and has a significant promoting effect on the adsorption process of bilirubin.

[0039] (2) The present invention has conducted an in-depth test on the bilirubin adsorption characteristics of the membrane coated with the coating solution with a mass ratio of 1:1. When the reaction temperature changes between 25°C and 42°C, the membrane's adsorption capacity for bilirubin shows a trend of first increasing and then decreasing, and reaches the highest point at a temperature of 37°C, i.e., 1.6 mg / g; when the NaCl concentration in the solution rises from 0.0 mol / L to 2.0 mol / L, the amount of bilirubin adsorbed by the affinity membrane begins to gradually decrease; in the concentration range of 10 mg / L to 50 mg / L, the higher the initial concentration of bilirubin, the stronger its adsorption capacity, and at an initial concentration of 50 mg / L, its adsorption performance reaches a peak of 1.9 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 IR spectra of pure PVA and s-PVA in Example 1;

[0041] Figure 2 IR spectra of blank PA11 membrane and s-PVA / PVAPA11 affinity membrane prepared in Example 1;

[0042] Figure 3 Contact angle of PA11 affinity membrane before and after coating with coating solution (A: blank membrane; B: SP-1-1);

[0043] Figure 4 Bilirubin standard curve;

[0044] Figure 5 Bilirubin adsorption at different temperatures;

[0045] Figure 6 Bilirubin adsorption in solutions with different ionic strengths;

[0046] Figure 7 Adsorption capacity of bilirubin solutions with different initial concentrations. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0048] Based on the information contained in this application, it is easy for those skilled in the art to make various changes to the precise description of the present invention without departing from the spirit and scope of the appended claims. It should be understood that the scope of the present invention is not limited to the defined process, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention. In fact, various changes that the technicians in this field or related fields can obviously make to the embodiments of the present invention are all covered within the scope of the appended claims.

[0049] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification and the appended claims are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0050] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. All raw materials used in the present invention are purchased from MacLean Reagent Company. For example, the PVA used in the present invention is purchased from MacLean Reagent Company, and its molecular weight is Mw=146,000-186,000 g / mol; the PA11 film used in the present invention has specifications of 30 mm and 0.1 nm.

[0051] Example 1

[0052] The present embodiment provides a method for preparing an s-PVA / PVA PA11 affinity membrane, the method specifically comprising the following steps:

[0053] (1) Preparation of sulfonated PVA (s-PVA)

[0054] 250 mL of anhydrous ethanol (EtOH) was added to a 500 mL three-necked flask with a thermometer and a condenser, and then 10 g of PVA was added to the anhydrous ethanol, and heated to 80° C. to fully swell, thereby obtaining a PVA / EtOH mixture.

[0055] 4.8 g of sodium hydroxide was slowly added to the PVA / EtOH mixture, and mechanical stirring was continued until the mixture was uniformly mixed. 1 g of 1,3-propane sultone was added dropwise to the reaction flask, and after the addition was completed, the resulting reaction solution was reacted at 80°C for 10 h; after the reaction was completed, the resulting product was washed with alcohol, filtered, and finally vacuum dried at 50°C for 12 h.

[0056] (2) Activation of PA11 membrane

[0057] Mix 20 mL of formaldehyde (≥36.5%, v / v) and 0.2 mL of phosphoric acid (≥85%, v / v), put into 10 PA11 membranes, and activate them in a 60°C water bath oscillator for 7 hours; after the activation, cool the reaction system to 40-50°C, wash with distilled water 2-3 times, and dry the activated PA11 membrane with filter paper;

[0058] The activated PA11 membrane obtained above was immersed in a 0.8 M boric acid solution, and then fixed on a flat glass. The excess boric acid solution was driven away with a glass rod, and then covered with a glass dish to prevent the PA11 membrane from drying out and set aside.

[0059] (3) Preparation of PA11 affinity membrane

[0060] Prepare 200 mL of 1.5% (W / V) chitosan solution, dissolve it in 2% (V / V) acetic acid solution, and then adjust the pH to 2.0 with 2 mol / L hydrochloric acid solution to obtain a 1% (W / V) chitosan acetic acid solution;

[0061] A piece of the activated PA11 membrane was immersed in the chitosan acetic acid solution and reacted at room temperature for 1 hour. After the reaction, the liquid on the membrane surface was ensured to flow slowly through the membrane pores by vacuum filtration technology, and then the dried membrane was placed in a 90° C. oven and taken out after 45 minutes.

[0062] The surface of the substrate was cleaned 3-5 times with 1% volume fraction acetic acid solution, followed by cleaning with distilled water for 4 hours.

[0063] (4) Preparation of s-PVA / PVA coating solution

[0064] The solution was prepared as shown in Table 1, with the mass ratios of s-PVA / PVA being 0 / 2, 0.40 / 1.60 (1:4), 0.50 / 1.50 (1:3), 0.67 / 1.33 (1:2) and 1.00 / 1.00 (1:1), respectively, and a 2 wt % blended solution was obtained after heating and stirring at 80° C. for 4 h to be used as a coating solution;

[0065] The pH of the s-PVA / PVA coating solution was adjusted to about 2 by adding 1.5 M HCl, and then an appropriate amount of glutaraldehyde (GA) was added to initiate the cross-linking reaction (the ratio of the molar amount of [-OH] in PVA to the molar amount of [GA] was 4:1), and the cross-linking time was monitored before coating.

[0066] (5) Preparation of s-PVA / PVA PA11 affinity membrane

[0067] At 25° C., when the optimal pre-crosslinking time reaches about 20 min, the pre-crosslinked coating solution is coated on the surface of the PA11 affinity membrane by a glass rod;

[0068] After coating, the wet membrane was sealed in a watch glass at room temperature for 12 h, then rinsed 2-3 times with phosphate buffered saline (PBS, pH=7.4) to remove residual HCl and GA to obtain the s-PVA / PVA PA11 affinity membrane, which was then placed in a water bath for use.

[0069] Table 1

[0070]

[0071] Test analysis:

[0072] (1) Fourier infrared test

[0073] Attenuated total reflection Fourier transform infrared spectroscopy was used to explore the surface structure of the s-PVA / PVA PA11 affinity membrane prepared in Example 1.

[0074] like Figure 1 As shown, the infrared spectrum clearly reveals the key peaks associated with PVA and s-PVA. -1 and 1200cm -1 A new peak was observed at the position.

[0075] At 1065cm -1 and 1200cm -1 The new peaks correspond to the symmetric and asymmetric stretching vibrations of O=S=O, respectively, which confirms the success of the sulfonation modification of PVA.

[0076] Polyvinyl alcohol (PVA) and propane sulfonate reacted in a nucleophilic substitution reaction to produce sulfonated PVA (s-PVA), which has been verified by infrared spectroscopy. This provides the necessary support for subsequent coating experiments.

[0077] Figure 2 The infrared spectrum analysis of the s-PVA / PVA PA11 affinity membrane prepared in Example 1 is shown. From these spectra, its molecular conformation and structural characteristics and its influence on the solvation reaction can be inferred. From the provided chart, we can observe that at 2925cm -1 and 2856cm -1 The stretching vibration is enhanced at the wave number position of about 1126cm -1 A new peak appeared in the location.

[0078] The grafting reaction between chitosan and its related derivatives and hydroxyethyl cellulose resulted in the -1 and 2856cm -1The stretching vibrations of CH2 and CH3 are enhanced at the wavenumber position. This indicates that carboxyl methylation can enhance its affinity for the amino group in amino acid molecules. A new peak appears at about 1126 cm -1 This provides a clue that there are sulfonic acid groups on the surface of the s-PVA / PVAPA11 affinity membrane.

[0079] It can be seen from the figure that the PA11 membrane has been successfully grafted with chitosan and the coating solution has also been successfully coated, which lays a solid foundation for subsequent experimental tests.

[0080] (II) Tensile performance test

[0081] At room temperature, the membrane was cut into thin strips of 30 mm long and 8 mm wide. A uniaxial tensile test was performed using a universal material testing machine. The tensile speed of the experimental equipment was set to 10 mm / min. By processing the test data, the elastic modulus and yield strength of the material at different strain rates and the corresponding stress-strain relationship were obtained. Instant readings of fracture were obtained.

[0082] Table 2 shows that the elongation at break of the blank PA11 film has reached 48%. In the experimental observation, as the ratio of s-PVA to PVA changes, we noticed that the elongation at break of various films fluctuated roughly within the range of 60.

[0083] Compared with the unmodified membrane, the modified membrane performed better in tensile strength, but the ratio of s-PVA to PVA had little significant effect on the tensile properties of the membrane; relative to the PA11 membrane, the s-PVA / PVA PA11 affinity membrane showed a significant increase in elongation at break.

[0084] Obviously, the s-PVA / PVA PA11 membrane manufactured by the present invention not only exhibits excellent selective permeability, but also has rich mechanical properties, which can fully meet the actual needs of the hemodialysis process. In the upcoming adsorption test, the strength support test is sufficient. The tensile performance data is shown in Table 2:

[0085] Table 2 Tensile properties of different films

[0086]

[0087] Table 3 Tensile properties of different films

[0088]

[0089] (III) Contact angle test

[0090] The hydrophilicity of the membrane was measured by a contact angle meter. The contact angle of water was tested respectively. The test conditions are shown in Table 4.

[0091] Table 4 Test conditions

[0092]

[0093] As can be seen from Table 5, the initial contact angle of the pure PA11 film is 70 degrees. However, when it is covered with the s-PVA / PVA film, the mass ratio of s-PVA / PVA increases from 1:4 to 1:1, and the initial contact angle of the improved composite film decreases from 70 degrees to 30 degrees.

[0094] The water contact angle (WCA) is a commonly used indicator to determine whether the membrane surface is hydrophilic. The lower the WCA of a membrane with similar structure, the stronger its hydrophilicity. When the contact angle is lower than 10°, the material is defined as superhydrophilic. By enhancing the hydrophilicity of the membrane, we can reduce the absorption and penetration resistance of organic pollutants to the membrane, thereby enhancing the membrane's anti-pollution ability and compatibility with blood. As the proportion of the coating solution gradually increases, the hydrophilicity of the membrane is also increasingly enhanced.

[0095] It can be concluded that the prepared SP-1-1 PA11 affinity membrane exhibits properties similar to superhydrophilic properties, providing basic conditions for subsequent experiments.

[0096] Contact angle related data are shown in Table 5:

[0097] Table 5 Contact angles of PA11 films coated with different coating solutions

[0098]

[0099]

[0100] (IV) Porosity test

[0101] The film thickness dL is directly measured using a micrometer with an accuracy of 0.01 mm. The porosity r is determined using the dry and wet film weight method. P : First measure the mass W1 of the dry film, then immerse the dry film in water, then take it out and wipe it dry, weigh the film weight W2, and calculate the porosity according to the following formula 1:

[0102]

[0103] Where V m is the apparent volume of the membrane; D water The density of water at a given temperature (usually 25°C).

[0104] According to Formula 1, the porosities of the blank nylon 11 membrane and the s-PVA / PVA PA11 affinity membrane prepared in Example 1 were calculated to be 0.94375 and 0.58875, respectively.

[0105] After experiments, the porosity of the s-PVA / PVA PA11 affinity membrane prepared in Example 1 decreased significantly. This low porosity has significant advantages in adsorption:

[0106] 1. Improve filtration accuracy: Smaller pore size means lower porosity, which helps to effectively intercept smaller particles or molecules during filtration.

[0107] 2. Improved selectivity: By adjusting the porosity, desired selectivity can be achieved in the filtration process, such as separating particles of different sizes or isolating specific solutes from a mixture.

[0108] 3. Reduce the accumulation of stains: Membranes with higher porosity are more likely to form scale because it provides a wider space for particles to settle. By reducing the porosity, we can reduce the associated risks, thereby reducing maintenance costs and extending the service life of the membrane.

[0109] 4. Improve anti-pollution ability: Reducing the porosity can help reduce the entry of pollutants into the interior of the membrane, thereby enhancing the membrane's anti-pollution ability.

[0110] 5. Optimize the permeability of the membrane: Although high porosity usually leads to higher permeability, too high a porosity may also lead to an increase in flow resistance. Moderately reducing the porosity can help improve the overall filtration effect of the membrane without sacrificing a lot of permeability.

[0111] (V) Drawing of bilirubin standard curve

[0112] Under light-proof conditions, 1 mg, 2 mg, 3 mg, 4 mg, and 5 mg of bilirubin were accurately weighed and placed in a brown volumetric flask, and then 2 mL of dimethyl sulfoxide and 3 mL of 0.5 mol / L sodium carbonate solution were added to completely dissolve it, and 3 mL of 0.1 mol / L HCl was used to neutralize the sodium carbonate, and phosphate buffer was added to make the volume to 100 mL. The absorbance of bilirubin at 440 nm was measured using a TU-1901 ultraviolet spectrophotometer, and a standard curve was drawn using software.

[0113] The bilirubin standard curve is as follows Figure 4 As shown. Figure 4 It can be seen that the linear regression formula is y = 0.08479x-0.3647, and the linear correlation coefficient R2 is 0.9544.

[0114] The R2 of the equation is quite close to 1, which shows that the model fits very well and the fit is very successful. It is very feasible to use this equation to calculate the bilirubin concentration.

[0115] The concentration obtained by this equation can be used as a reference for the concentration of bilirubin solution, which provides a solid foundation for the subsequent bilirubin adsorption condition test.

[0116] (VI) Effect of temperature on adsorption effect

[0117] Take the s-PVA / PVA PA11 affinity membrane prepared in Example 1, add 10mL, 0.030g / L bilirubin standard solution, adjust the solution pH to 7.4, and carry out 2.5 hours of oscillation reaction in a water bath environment at different temperatures (22°C, 27°C, 32°C, 37°C, 42°C), and then filter. At a wavelength of 440nm, the absorbance of the filtrate was measured, and the mass concentration of the bilirubin solution was calculated accordingly. Finally, the adsorption amount was estimated according to Formula 2. The optimal adsorbent preparation conditions and the optimal operating parameters were determined experimentally, and a complete set of adsorption kinetic models was established. Using software, with the adsorption temperature as the horizontal axis and the adsorption amount as the vertical axis, a relationship curve between the adsorption temperature and the adsorption amount of bilirubin by the PA11 affinity membrane was drawn.

[0118] Figure 5 Bilirubin adsorption at different temperatures. Figure 5 The adsorption behavior of bilirubin by the s-PVA / PVA PA11 affinity membrane prepared in Example 1 under different temperature conditions is demonstrated. When the temperature rises from 25°C to 42°C, the adsorption capacity of the affinity membrane for bilirubin shows a trend of first rising and then falling, and reaches a peak at 37°C. As the temperature gradually rises, the adsorption amount of bilirubin by the affinity membrane also continues to increase, reaching an adsorption peak of 1.6 mg / g at a temperature of 37°C, but in the subsequent temperature range of 37-42°C, the adsorption amount begins to gradually decrease.

[0119] The adsorption capacity of the s-PVA / PVA PA11 affinity membrane prepared in Example 1 for bilirubin is enhanced when the temperature rises, but if the temperature is too high, bilirubin may decompose to some extent, resulting in a decrease in the adsorption amount. When the temperature is 37°C, it is close to human body temperature, which is conducive to the use of affinity membranes in artificial livers.

[0120] The temperature test provides a valuable reference for determining the test conditions of other variables. The following tests will be completed at 37°C.

[0121] (VII) Effect of ionic strength in solution on adsorption effect

[0122] Take the s-PVA / PVA PA11 affinity membrane prepared in Example 1, add 10mL, 0.03mol / L bilirubin standard solution, add sodium chloride with concentrations of 0.00mol / L, 0.05mol / L, 0.10mol / L, 0.15mol / L, 0.20mol / L, and 0.25mol / L, respectively, adjust the pH value to 7.4, maintain the temperature in a water bath at 37°C for 2.5h, filter, take the filtrate and measure its absorbance at 440nm, calculate the mass concentration of the bilirubin solution, and then calculate the adsorption amount according to Formula 2. With sodium chloride concentration as the horizontal axis and adsorption amount as the vertical axis, use software to draw a curve to analyze the influence of ionic strength on the adsorption effect.

[0123] Figure 6 A schematic diagram showing how ionic strength affects the adsorption of bilirubin by the s-PVA / PVA PA11 affinity membrane prepared in Example 1. From the provided chart, we can clearly observe that when the concentration of NaCl rises to 2.0 mol / L, the absorption capacity of the s-PVA / PVA PA11 affinity membrane for bilirubin gradually decreases. In a bilirubin solution with an initial concentration of 30 mg / L, the concentration of NaCl continues to rise, resulting in a gradual decrease in the amount of bilirubin adsorbed by the s-PVA / PVA PA11 affinity membrane. When the ion concentration drops to 0, the adsorption of the s-PVA / PVA PA11 affinity membrane reaches a peak of 1.4 mg / g.

[0124] The ion concentration test provides a valuable reference for determining the test conditions of other variables in the future. The subsequent tests will not be conducted without the addition of NaCl.

[0125] (VIII) Effect of initial concentration of bilirubin solution on adsorption effect

[0126] Take the 10mm×10mm s-PVA / PVA PA11 affinity membrane prepared in Example 1, add 10mL of bilirubin standard solution with concentrations of 0.05g / L, 0.10g / L, 0.15g / L, 0.20g / L, and 0.25g / L, respectively, adjust the pH value to 7.4, maintain the temperature at 37°C in a water bath for oscillation reaction for 2.5h, filter, take the filtrate to measure its absorbance at 440nm, calculate the mass concentration of the bilirubin solution, and then calculate the adsorption amount according to Formula 2. With the concentration of the bilirubin solution as the horizontal axis and the adsorption amount as the vertical axis, use software to draw a curve to analyze the effect of bilirubin concentration on the adsorption effect.

[0127] The bilirubin adsorption capacity of PA11 affinity membrane can be calculated by formula 2.

[0128]

[0129] Figure 7 The graph shows the adsorption behavior of the s-PVA / PVA PA11 affinity membrane prepared in Example 1 at different initial bilirubin solution concentrations. When the initial concentration of the bilirubin solution increases from 10 mg / L to 50 mg / L, the affinity membrane's absorption capacity for bilirubin gradually increases. When the initial concentration rises to 50 mg / L, the adsorption capacity of the s-PVA / PVA PA11 affinity membrane for bilirubin reaches a peak, specifically 1.9 mg / g.

[0130] The present invention successfully uses PA11 as the base material of the affinity membrane, and after activation, hydrolysis and grafting chitosan, five different ratios of s-PVA / PVA solutions are prepared to coat the affinity membrane. The present invention enhances the hydrophilicity and anti-pollution ability of the membrane, and studies the mechanical properties, porosity and adsorption capacity of bilirubin of the prepared s-PVA / PVA PA11 affinity membrane, thereby drawing the following conclusions:

[0131] After activation treatment of PA11 membrane, the grafting rate of chitosan reached 81.8%, which significantly improved the biocompatibility of the affinity membrane; as the ratio of s-PVA / PVA increased from 0:2 to 1:1, the contact angle of the s-PVA / PVA PA11 affinity membrane decreased from 45° to 30°, and the elongation at break also increased from 47% to 60%; after coating treatment, the porosity of the s-PVA / PVA PA11 affinity membrane decreased from 0.9 to 0.6, thereby improving the filtration capacity of the membrane; within the reaction temperature range from 25°C to 42°C, the adsorption capacity of the s-PVA / PVA PA11 affinity membrane for bilirubin showed a trend of first increasing and then decreasing, and reached its maximum value of 1.6 mg / g at 37°C; as the concentration of NaCl in the solution increased from 0.0 mol / L to 2.0 mol / L, the adsorption capacity of the s-PVA / PVA PA11 affinity membrane for bilirubin gradually decreased. In the concentration range of 10 mg / L to 50 mg / L, the higher the initial concentration of bilirubin, the stronger its adsorption capacity is, and at an initial concentration of 50 mg / L, its adsorption performance reaches its peak, which is 1.9 mg / g.

Claims

1. A method for preparing an s-PVA / PVA PA11 affinity membrane, characterized in that: The method specifically comprises the following steps: (1) Preparation of PA11 affinity membrane Prepare an acetic acid solution of chitosan, adjust the pH value to 2, place the activated PA11 membrane in the acetic acid solution of chitosan, and react at room temperature for 0.5-1.5 hours; after the reaction is completed, filter under reduced pressure, dry, and wash to obtain the PA11 affinity membrane; (2) Preparation of s-PVA / PVA coating solution Mix sulfonated PVA (s-PVA), polyvinyl alcohol (PVA) and deionized water according to a ratio, heat and stir to mix, and obtain the s-PVA / PVA coating solution; (3) Preparation of s-PVA / PVA PA11 affinity membrane The pH value of the s-PVA / PVA coating solution in step (2) is adjusted to 1.5-2.5, and then glutaraldehyde (GA) is added according to the ratio, and the resulting mixed reaction solution undergoes a pre-crosslinking reaction at room temperature; after the pre-crosslinking reaction is completed, the resulting pre-crosslinking coating solution is coated on the surface of the PA11 affinity membrane in step (1), and finally the solution is sealed and dried at room temperature, and washed to obtain the s-PVA / PVA PA11 affinity membrane.

2. The preparation method according to claim 1, characterized in that: The preparation method of the activated PA11 film in step (1) is as follows: Formaldehyde and phosphoric acid are mixed according to a ratio, heated to 55-65° C., a PA11 membrane is placed in the resulting mixed solution, oscillated at a constant temperature for 5-10 hours, then cooled to 40-50° C., washed, and finally dried with filter paper to obtain the activated PA11 membrane.

3. The preparation method according to claim 1, characterized in that: The mass ratio of s-PVA to PVA in step (2) is 1:4-1:

1.

4. The preparation method according to claim 3, characterized in that: The mass ratio of s-PVA to PVA in step (2) is 1:

1.

5. The preparation method according to claim 1, characterized in that: The preparation method of s-PVA in step (2) is as follows: PVA is mixed with anhydrous ethanol (EtOH) according to a ratio, heated to swell, and a PVA / EtOH mixture is obtained; sodium hydroxide is then added according to a ratio, mixed evenly, propane sultone is added dropwise to the obtained mixture, and heating is continued for 6-10 hours after the addition is completed; after the reaction is completed, the s-PVA is obtained by washing with alcohol, filtering, and vacuum drying.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the PVA to the propane sultone solution is 10:

1.

7. The preparation method according to claim 1, characterized in that: The ratio of the molar amount of [-OH] to the molar amount of [GA] in the PVA in step (3) is 4:

1.

8. The s-PVA / PVA PA11 affinity membrane prepared by the method according to any one of claims 1 to 7.

9. Use of the s-PVA / PVA PA11 affinity membrane prepared by the method according to any one of claims 1 to 7 in adsorbing bilirubin.

10. An adsorbent for adsorbing bilirubin, characterized in that: The adsorbent includes the s-PVA / PVA PA11 affinity membrane prepared by the method according to any one of claims 1 to 7.